Proceedings of the Fifth International ACM Conference on Assistive Technologies 2002
DOI: 10.1145/638249.638274
|View full text |Cite
|
Sign up to set email alerts
|

Cursor measures for motion-impaired computer users

Abstract: Point and click" interactions remain one of the key features of graphical user interfaces (GUIs). People with motion-impairments, however, can often have difficulty with accurate control of standard pointing devices. This paper discusses work that aims to reveal the nature of these difficulties through analyses that consider the cursor's path of movement. A range of potential cursor measures was applied, and a number of them were found to be significant in capturing the differences between able-bodied users an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 7 publications
(11 reference statements)
1
38
0
Order By: Relevance
“…3 of the previous section, even with the adjustment for effective target width, it would appear that there is still a requirement for the error rate to be reasonably low. Compared with able-bodied users, however, motion-impaired users exhibit a greater tendency to click outside the target, and can average more than one click outside the target per trial [9]. In this case, the error rate as defined in ISO 9241-9 would be 100%, and MT and TP would only measure how quickly users can click in an area outside the target.…”
Section: Fitts' Law and The Iso 9241-9 Standardmentioning
confidence: 99%
See 2 more Smart Citations
“…3 of the previous section, even with the adjustment for effective target width, it would appear that there is still a requirement for the error rate to be reasonably low. Compared with able-bodied users, however, motion-impaired users exhibit a greater tendency to click outside the target, and can average more than one click outside the target per trial [9]. In this case, the error rate as defined in ISO 9241-9 would be 100%, and MT and TP would only measure how quickly users can click in an area outside the target.…”
Section: Fitts' Law and The Iso 9241-9 Standardmentioning
confidence: 99%
“…If a click occurred when the cursor was outside the target, the user had to correct the position of the cursor and click again. Consequently, there were no ''error'' trials as defined in ISO 9241-9 [5], but the number of clicks per trial occurring outside the target served as a measure of error [9]. The time to complete each trial, the number of mouse clicks in each trial, and the cursor position throughout the trial were automatically logged by the software.…”
Section: Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…Haptic feedback has the potential to provide redundant feedback, which would greatly improve the saliency of signals, as well as provide a unique feedback as a new signal to reinforce or improve user understanding (Robles-de-la-Torre, 2006). Haptic technology has found many successful applications such as surgical simulation (e.g., Basdogan et al, 2004;Chebbi et al, 2005), medical training (e.g., Coles, Meglan, & John, 2011), virtual prototyping (Zhu & Lee, 2004), scientific visualization (e.g., Lawrence, Pao, Lee, & Novoselov, 2004), and assistive technology for users with visual impairments (e.g., Amemiya & Sugiyama, 2010) or motionimpaired users (e.g., Keates, Hwang, Langdon, Clarkson, & Robinson, 2002). Many studies have also shown that haptic feedback can improve user performance in various tasks (Dinse et al, 2005;Richard & Coiffet, 1995), enhance the sense of sharing and each user's perception on his or her partner's actions (Hubbold, 2002), and increase perceived togetherness (Basdogan, Ho, Srinivasan, & Slater, 2000;Sallnas, RassmusGröhn, & Sjöström, 2000;Slater, Sadagic, Usoh, & Schroeder, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Even basic pointer navigation may turn into an arduous task, and concentrating on performing targeting tasks can cause exhaustion. Some work has been conducted in the area of filtering and analysis of tremor, most of which is software based [4,8,16], with a smaller amount that uses a hardware approach [9]. These works involved the testing of a mouse or mouse-like devices.…”
Section: Introductionmentioning
confidence: 99%